2001
DOI: 10.1002/1097-0282(200109)59:3<131::aid-bip1013>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thermal history on the structural and mechanical properties of agarose gels

Abstract: Using a multitechnique approach, two temperature domains have been identified in agarose gelation. Below 35°C, fast gelation results in strong, homogeneous and weakly turbid networks. The correlation length, evaluated from the wavelength dependence of the turbidity, is close to values of pore size reported in the literature. Above 35°C, gelation is much slower and is associated with the formation of large‐scale heterogeneities that can be monitored by a marked change in the wavelength dependence of turbidity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
147
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(160 citation statements)
references
References 54 publications
13
147
0
Order By: Relevance
“…Evidence for agarose possessing temperature dependant properties is available in the literature. It has been reported that fast gelation at temperatures below 35ºC can result in the formation of a stiffer, more homogenous gel compared to gels cured at temperatures above 35ºC (Aymard et al 2001). That study found that the elastic modulus, as determined from ramp compression tests, varied with the curing temperature from 12 to 82 kPa, with the highest values obtained at curing temperatures between 5 and 15ºC.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for agarose possessing temperature dependant properties is available in the literature. It has been reported that fast gelation at temperatures below 35ºC can result in the formation of a stiffer, more homogenous gel compared to gels cured at temperatures above 35ºC (Aymard et al 2001). That study found that the elastic modulus, as determined from ramp compression tests, varied with the curing temperature from 12 to 82 kPa, with the highest values obtained at curing temperatures between 5 and 15ºC.…”
Section: Discussionmentioning
confidence: 99%
“…Natural gels, such as agarose [26] and the calcium alginates, do seem to form ordered regions of double helix or multiple helices [27][28][29]. As a result, the mechanical properties are very dependent on the extent of structure developed during gelation [30]. The disruption of these structures during fracture could be expected to be a source of energy absorption and so increase strength and toughness.…”
Section: Strengthmentioning
confidence: 99%
“…In fact both G' and G'' are at least three orders of magnitude lower than at conventional gel state below 30˚C. Aymard et al [20] measured G' at similar conditions but did not show this behavior probably because their instrument was not sensitive enough to detect the these orders of magnitude lower G' mentioned above. Though the cooling rate in our rhological measurements was not as low as those in light …”
Section: Resultsmentioning
confidence: 99%
“…Thus, the higher-order structure and physical properties of agarose gel depend strongly on the thermal history. While Aymard et al [20] demonstrated certain structure formation in very slow cooling or elongated curing at around 40˚C, quantitative information on the influence of cooling rate and the temperature range for this process has not been reported. In this study, we examined the structural evolution of a 1.0wt% aqueous agarose solution by a stepwise cooling with a rate less than 0.008˚C/min, and two distinct atages were obserbed before final gelation.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation